Ù…ØØ§ÙˆÙ„Ø§Øª ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¹Ø§Ù„ÙŠ Ù„Ù„Ø£Ø³Ø¹Ø¯ÙŠØ© Ø³Ù†ÙƒØ§Ù…Øº Ø³Ù„Ø§ÙˆÙŠØ³ÙŠ Ø§Ù„Ø¬Ù†ÙˆØ¨ÙŠØ© - Kaharuddin, Kaharuddin (IAIN Salatiga, 2019)
The aim of this study was to determine the process of learning speaking skills in this program and its efforts in developing speaking skills. In this study, the authors used descriptive qualitative research methods, with historical, methodological, and opinion approaches. The results showed that speaking skills in the Ma’had Aliy As'adiyah Sengkang-South Sulawesi Program were related to the use of curriculum, learning methods, instructional media, and teaching materials. Meanwhile, the program's efforts in developing speaking skills consist of three parts, namely 1. efforts in practicing Arabic language directly, 2. Efforts to carry out various activities in the use of Arabic, 3. Efforts in the form of solution, namely efforts that will be carried out next by Ma’had Aliy As'adiyah Sengkang, South Sulawesi to improve the previous efforts that have not been effective and successful.